A citizen science approach to enhance dolphinfish (Coryphaena hippurus) data collection to improve species management. (20th April 2022) - Merten, Wessley; Appeldoorn, Richard; Latour, Jacob; Glaser, Collin; Becker, Emily; Hammond, Don
Abstract: Public integration in scientific research is fundamental to the conservation and enhancement of marine fisheries. A comprehensive review of the world's largest international citizen science capture–mark–recapture program (Dolphinfish Research Program (DRP)) for dolphinfish ( Coryphaena hippurus ) was completed to catalogue 16 years of conventional tagging data and angler participation from 2002 to 2017. Data showed at least 1313 captains, 1332 vessels and more than 3285 fishing mates from around the world participated in the tag and release of 23, 232 dolphinfish. Of those fish, 571 were recaptured and 19 horizontal movement categories were used to reveal detailed descriptions of movements of dolphinfish in the wild. Our review identified science‐based outcomes and established future research and outreach direction with the public. The combination of new studies, strategies and initiatives identified through this review will help advance our understanding of dolphinfish and provide the necessary data to ensure the long‐term conservation of this critically important offshore fish species.